Spirometric reference values for healthy nonsmoking Saudi adults. (31st July 2013) - Al Ghobain, Mohammed O.; Alhamad, Esam H.; Alorainy, Hassan S.; Al Hazmi, Manal; Al Moamary, Mohamed S.; Al‐Hajjaj, Mohamed S.; Idress, Majdy; Al‐Jahdali, Hamdan; Zeitouni, Mohammed
Abstract Objectives To derive prediction equations of spirometric values of healthy Saudi adults and to compare the derived equations with equations reported in selected population. Methods Cross‐sectional study of healthy nonsmoking men and women Saudi adults. The measured spirometric values were the forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), peak expiratory flow (PEF) and forced mid‐expiratory flow (FEF 25%–75%). Results A total of 621 spirometric tests were done. The prediction equations were derived using the following formula: Predicted spirometric value = constant + (b1 × age) + (b2 × height (cm)), where b1 and b2 represent the regression coefficients for age and height, respectively. <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> <thead> Variable Constant Age (years) Height (cm) Variable Constant Age (years) Height (cm) </thead> Males (n = 292) Females (n = 175) FVC −2.933 −0.018 0.046 FVC −3.470 −0.016 0.045 FEV1 −1.886 −0.019 0.036 FEV1 −2.482 −0.018 0.036 FEV1/FVC (%) 98.41 −0.095 −0.068 FEV1/FVC (%) 100.67 −0.142 −0.072 PEF 17.274 −1.243 3.471 PEF −226.648 −0.499 4.076 FEF25%–75% 0.100 −0.024 0.027 FEF25%−75% −1.337 −0.021 0.031 </table-wrap> The means of the measured FVC and FEV1 were significantly lower than the predicted values derived by the American equations of −7.2% and −4.6% among males, respectively (P value < 0.00001), and −4.7%, and −5.26% among females, respectively (P value < 0.00001). Conclusion The reference spirometric values derived in our study were significantly lower than the predicted values derived by the American equations.